Real-Time Capture and Visualization of Individual Viruses in Complex Media - Scherr, Steven M. (ACS Nano, 2016)
Label-free imaging of individual viruses and nanoparticles directly in complex solutions is important for virology research and biosensing applications. A successful visualization technique should be rapid, sensitive, and inexpensive, while needing minimal sample preparation or user expertise. Current approaches typically require fluorescent labeling or the use of an electron microscope, which are expensive and time-consuming to use. We have developed an imaging technique for real-time, sensitive, and label-free visualization of viruses and nanoparticles directly in complex solutions such as serum. By combining the advantages of a single-particle reflectance imaging sensor, with microfluidics, we perform real-time digital detection of individual 100 nm vesicular stomatitis viruses as they bind to an antibody microarray. Using this approach, we have shown capture and visualization of a recombinant vesicular stomatitis virus Ebola model (rVSV-ZEBOV) at 100 PFU/mL in undiluted fetal bovine serum in less than 30 min.